2000
DOI: 10.1007/pl00013669
|View full text |Cite
|
Sign up to set email alerts
|

Undulation instability under shear: A model to explain the different orientations of a lamellar phase under shear?

Abstract: We study the effects of a dilation on a sheared smectic A phase. Through a linear analysis, we show that undulation may grow in the direction of the flow and of the vorticity as found in previous works. At higher shear rates, we evidence that the undulation along the flow disappears whereas it persists in the vorticity direction. We determine the stable or unstable zone as a function of the shear rate and of the lamellar spacing. This allows us to draw a theoretical shear diagram of the instability. Finally we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 14 publications
0
44
1
1
Order By: Relevance
“…It is important to note that although quite general [4,5], this behaviour is not universal and remains very system-dependent [6][7][8]. Moreover, the mechanism of onions formation is still under a theoretical debate [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that although quite general [4,5], this behaviour is not universal and remains very system-dependent [6][7][8]. Moreover, the mechanism of onions formation is still under a theoretical debate [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of the layer orientation transition in the lyotropic lamellar phase was theoretically argued by some researchers [13][14][15]. Ramaswamy argued that the suppression of undulations triggers the transition [13].…”
Section: Resultsmentioning
confidence: 99%
“…Oswald et al proposed that defects generated from flowing smectic in misaligned plates also induce the dilation strain [19]. Wunenburger and co-workers extended this idea and demonstrated that the shear induces destabilization in the flow direction [15]. We have also recently presented that the defect formation is essential for the shear-induced onion formation [10].…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations